Literacy Community Empowerment to Strengthen Early Age Literacy Culture in RT 30 RW 16 Sikumana Village Kupang City: Pemberdayaan Komunitas Literasi Untuk Penguatan Budaya Literasi Pada Usia Dini di RT 30 RW 16 Kelurahan Sikumana Kota Kupang - Willem Amu Blegur; Sarci Magdalena Toy; Cici Manimau (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The community has not fully realized the importance of literacy culture and how to develop it, especially among early childhood. Literacy activities are still considered boring activities. The lack of improvisation in literacy activities causes literacy to become rigid. This community service activity is related to the issue of increasing literacy habits in community groups. The stages of the activity include a) conducting discussions with religious communities to identify literacy issues, b) planning the implementation of activities at the location together, c) implementing activities, and d) conducting monitoring and evaluation surveys of activity results. The results of the activity showed that there was an increase in perception and action plans to cultivate literacy in the community in RT 30 RW 16 Sikumana Village, Kupang City. Awareness of the importance of literacy is used as a momentum to provide teaching and activities together with religious-based communities so that parents and children slowly cultivate literacy.